Reduced composite dietary antioxidant index increases the risk of Parkinson’s disease and all-cause mortality in Parkinson’s disease patients: evidence from the NHANES database - Fei Huang; Jingwen Hao; Chanjuan Chen; Qun Liu; Dan He (Frontiers in Aging Neuroscience)
BackgroundThis study aimed to investigate the relationship between the Composite Dietary Antioxidant Index (CDAI) and the prevalence of Parkinson’s disease (PD), as well as to explore its relationship with all-cause mortality risk in PD patients.MethodsData from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2007 to 2018 were used, including 119,609 participants. After excluding individuals aged <18 years, those with incomplete follow-up data, and those missing critical variables such as CDAI and covariates, the final cohort consisted of 34,133 participants. Participants were categorized into a PD group (510 individuals) and a non-PD group (33,623 individuals). The CDAI values were calculated, and participants were divided into three groups based on the tertile distribution of their CDAI scores: Q1 (CDAI < −1.07), Q2 (−1.07 to 1.74), and Q3 (CDAI >1.74). Weighted logistic regression and weighted Cox regression analyses were employed to evaluate the associations between CDAI and the prevalence of PD, as well as between CDAI and all-cause mortality risk. Restricted cubic spline regression analysis was used to further elucidate the precise relationship between CDAI and outcome events.ResultsCDAI values were significantly lower in the PD group compared to the non-PD group. After adjusting for age, sex, comorbid conditions (hypertension and diabetes), blood lipid and glucose levels, a reduction in CDAI was associated with an increased risk of PD (Q3 vs. Q1, OR = 0.72, p = 0.035). In patients with PD, a decrease in CDAI was significantly associated with a higher risk of all-cause mortality (Q3 vs. Q1, HR = 0.53, p = 0.018). This association was particularly pronounced in those over 60 years old, smokers, and those with hypertension. Restricted cubic spline regression analysis identified CDAI <0.471 as a risk factor for PD, and CDAI <0.527 as a risk factor for all-cause mortality in PD patients.ConclusionCDAI reduction is an independent risk factor for both PD risk in the general population and all-cause mortality in PD patients, with amplified predictive power in older adults, smokers, and hypertensive individuals. Our findings support developing personalized antioxidant-enhancing nutritional interventions for both high-risk populations with suboptimal CDAI and established PD patients.